Dynamics of a Delayed Prey-Predator System With Crowley-Martin Functional Response - Abas, Bryar Khdhir; Hassan, Kawa Ahmad (Iraqi Journal of Science, 2024)
ln this paper, an ecological predator-prey model with time delay is proposed and studied analytically and numerically. The stability and bifurcation analysis of the proposed model with a Crowley-Martin response function are covered in this article. In the beginning, equilibrium points of the proposed model are identified. Secondly, the local asymptotic stability of the equilibria and Hopf-bifurcation are discussed by the characteristic equations of the system. Finally, by creating a suitable Lyapunov function and LaSalle’s invariance principle, the equilibria’s global asymptotic stability is examined.